Perception of the general population and health professionals on how to obtain organs for transplantation: A marketing perspective - Andrade, Daniela Alves Pereira de; Goldim, José Roberto (Brazilian Journal of Transplantation, 2018)
Purpose: This article presents the perceptions of health professionals and the public as to the method to obtain organs, especially the market approach. Methods: To preset data on the selflessly perception of the participants and including the involvement of personal or family need to obtain organs for transplantation by using the market approach. To meet the objectives of this study, a questionnaire was developed to collect the opinions of participants. Its distribution was personally performed in a random way, and it was also developed an electronic version released via Facebook page. The analysis of the responses were discussed at a 5% significance, and considered significant whenever p was <0.05. Results: Overall, 692 people participated in the survey. In the health professional category there are more likely than among the general population to disagree on the indirect incentives related to the tax reduction and 30-days paid leave. These were the only significant associations related to health professionals. Most participants (80.1%) agreed that organ donation must be a selfless act and strictly supportive, but 52% believe that the market could be a fair and beneficial system for all. In an extreme situation of absolute shortage of organs, 54.9% of respondents indicated they would pay for an organ to save his/her life or the life of a family member. Conclusion: Collectively, participants broadly support the solidary donation condemning the possibility of payment or remuneration associated to the funding, but most people would pay for an organ in extreme personal cases or upon a family need. This demonstrates the need for further reflection on the ethical problems associated to the issues involved in the organ procurement aiming to perform transplants.